The Analysis of the Licensing System in Healthcare Worker Practice License Services in Lumajang Regency - Setiawan, Galih Wahyu; Hamdhani, Rofiqa Marta; Hayat, Hayat (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
Licensing Practice Licenses (SIP) for healthcare workers is crucial in ensuring the legality and quality of healthcare services provided to the community. Lumajang Regency, one of Indonesia's regions, has various regulations and procedures related to the issuance of SIP that follow national rules and regional policies. This research aims to explore and analyse the SIP licensing process in Lumajang Regency using the literature review method from several references available in SINTA journals. The literature review method is conducted to obtain a comprehensive picture of the challenges, policies, and regulations related to SIP issuance for healthcare workers. The research results indicate several factors influencing the licensing process, including administrative constraints, compliance with regulations, and regional policy support. This research is expected to contribute to the development of more effective health worker licensing policies in Lumajang Regency.